Gleanings from the history of Armenian-German archaeological relations - Bobokhyan, Arsen (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
Armenian-German archaeological contacts go back some 200 years. Interest by German archaeologists in Armenia, and the Caucasus in general, is based on several factors. On the one hand, Armenia was an important part of the ancient world, and, together with its cuneiform tradition, it readily became the focus for archaeological research. Moreover, during the 19th century Armenia and the Caucasus evolved into an area where answers to many questions related to newly discovered ancient cultures were looked for. Additionally, there had been a cluster of German communities in the region since the beginning of the 19th century – as well as German economic and political interests. In the meantime, for the Armenian society Germany represented one of the most important centres of the modern civilised world, especially in terms of its prestigious universities that attracted many Armenian students keen to study, acquire qualifications, and return to their native land to usher in change and develop their country.